How 3D Printing Is Reshaping Translational Research - Sigston, Elizabeth A. W. (Frontiers in Bioengineering and Biotechnology, 2021)
“Translational Research” has traditionally been defined as taking basic scientific findings and developing new diagnostic tools, drugs, devices and treatment options for patients, that are translated into practice, reach the people and populations for whom they are intended and are implemented correctly. The implication is of a unidirectional flow from “the bench to bedside”. The rapidly emergent field of additive manufacturing (3D printing) is contributing to a major shift in translational medical research. This includes the concept of bidirectional or reverse translation, early collaboration between clinicians, bio-engineers and basic scientists, and an increasingly entrepreneurial mindset. This coincides with, and is strongly complemented by, the rise of systems biology. The rapid pace at which this type of translational research can occur brings a variety of potential pitfalls and ethical concerns. Regulation surrounding implantable medical devices is struggling to keep up. 3D printing has opened the way for personalization which can make clinical outcomes hard to assess and risks putting the individual before the community. In some instances, novelty and hype has led to loss of transparency of outcomes with dire consequence. Collaboration with commercial partners has potential for conflict of interest. Nevertheless, 3D printing has dramatically changed the landscape of translational research. With early recognition and management of the potential risks, the benefits of reshaping the approach to translational research are enormous. This impact will extend into many other areas of biomedical research, re-establishing that science is more than a body of research. It is a way of thinking.